2020
DOI: 10.1177/1074295620915883
|View full text |Cite
|
Sign up to set email alerts
|

Using Teacher Praise With Middle and High School Students

Abstract: Teacher praise is an evidence-based strategy shown to increase appropriate prosocial behavior and decrease disruptive behavior, particularly with elementary school age students. In this article, we provide direction and recommendations for using positive feedback with middle and high school students. A review of the research literature, guidelines for implementation, and online resources are presented, along with a case study example designed to apply the implementation guidelines in a secondary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 45 publications
2
27
0
1
Order By: Relevance
“…General praise only acknowledges that a student has done something correct. Whereas, behavior‐specific praise provides students with specific information about what they did correctly or what appropriate classroom behavior they exhibited, and this allows students to understand how to apply or demonstrate similar behaviors in future situations (Haydon et al, 2020). The results of previous intervention studies indicated that as teachers increased their use of behavior‐specific praise, students increased their on‐task behavior (Allday et al, 2012; Sutherland et al, 2000; Thompson et al, 2012), and decreased off‐task or disruptive behavior (Austin & Soeda, 2008; Reinke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…General praise only acknowledges that a student has done something correct. Whereas, behavior‐specific praise provides students with specific information about what they did correctly or what appropriate classroom behavior they exhibited, and this allows students to understand how to apply or demonstrate similar behaviors in future situations (Haydon et al, 2020). The results of previous intervention studies indicated that as teachers increased their use of behavior‐specific praise, students increased their on‐task behavior (Allday et al, 2012; Sutherland et al, 2000; Thompson et al, 2012), and decreased off‐task or disruptive behavior (Austin & Soeda, 2008; Reinke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, we recorded that the study with the greatest frequency of both general praise and behavior‐specific praise had the youngest participants in this synthesis (3–5 year olds; Floress, Beschta, et al, 2017); these results are similar to other studies that reported teachers to use more praise with younger students, compared to older students (e.g., McLennan et al, 2020). Other researchers have also reported on the paucity of research with middle and high school students related to teachers' use of praise (Haydon et al, 2020); future researchers may consider adding to the research base in this area so that more targeted recommendations can be provided for teachers who work with older students. Teachers may be cognizant of the fact that older students also respond well to teacher praise and look for opportunities to appropriately incorporate it into their daily instructional routines.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested in Firdaus (2015), praise can be seen as an extrinsic reward (verbal or written) that helps control students' behaviors, performances, and transfer instructional information better. The concept extends beyond "teacher feedback" in that it includes elements of affect, passion, explicit positive performance feedback, and builds on students' self-image and self-esteem (Zoder-Martell et al, 2019;Haydon et al, 2020). Moreover, as pinpointed by Ennis et al (2019), praise is a simple strategy to inspire prosocial behaviors among the students and prevent their classroom disruptive behaviors.…”
Section: Background the Concept Of Praisementioning
confidence: 99%
“…The construct of praise is by no means a simple strategy to control or manipulate the learners but a research-based, naturalistic technique to develop positive and meaningful interpersonal communication and rapport between the teacher and his/he students in the class (Haydon et al, 2020). Aside from the typologies of teacher praise, educators and practitioners must take into consideration a number of critical factors that significantly affect the quality and efficacy of their given praise to the students.…”
Section: Critical Factors Influencing Teacher Praise Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation